New street scene for pedestrians and drivers - Stanić, Branimir; Vukanovic, Smiljan; Osoba, Miroslav (Transport, 2005)
In the last twenty years all cities throughout the world have faced a continual increase in traffic demand. Neither a simple increase in physical capacities of the traffic network nor introduction of new traffic control systems nor similar isolated actions can be the right response to the increased traffic demands. New approaches to traffic management and application of complex new technological solutions in traffic control are called for. Besides improving safety for all participants, their main objectives are to increase the capacity of the existing infrastructure to enable its efficient exploitation in accordance with the current traffic demand and to protect urban environment from unnecessary traffic aggressive influence. It is clear that to achieve traffic flow the following issues should be taken into consideration: (1) Traffic conditions (to reduce duration and scope of traffic jams, to increase capacity and level of safety); (2) Physical surroundings (less noise and less pollution), and (3) Economic conditions (efficient usage of time, energy, space and other resources). Management of traffic means the possibility to choose an adequate management algorithm and the possibility to adapt it to the constant changes in traffic demand and not so dynamic changes in urban surrounding demand. First Published Online: 27 Oct 2010